KEY AREAS OF INTERNATIONAL COOPERATION WITHIN THE FRAMEWORK OF SHANGHAI COOPERATION ORGANISATION - O. U. Kolegova (MGIMO University Press, 2013)
The article reviews the current and future directions of the Shanghai Cooperation Organization (SCO) member states’ cooperation. The author emphasizes the need of the comprehensive, multi-faceted approach to the de-velopment and expansion of contacts of the countries participants of the organization. Analysis of the key areas of cooperation showed that the greatest prospect projects are in the areas of interaction such as infrastructure construction, transport, energy, technology, agriculture, humanitarian, cultural, and military cooperation. However, the article implies that the economic cooperation within the SCO is the weakest area of activity of the organization, the multilateral economic projects successfully implemented, in fact, are not yet available, as the bilateral cooperation is often implemented without the SCO (despite the fact that the SCO will promote its activation). The author believes that the connection to the SCO such national economies as India and Pakistan can greatly stimulate the development of economic cooperation, to give impetus to the beginning of a number of important multilateral projects. In addition, one of the main causes of economic cooperation deceleration in the SCO, he said the lack of dedicated funding mechanism for multilateral projects.The paper identified the medium-term prospects for international cooperation within the SCO, which have become more apparent in June 2012, at the regular meeting of the SCO Council of State’ Heads, held in Beijing, a brief review of the approved there important documents defining trends of the organization over the next decade.